HUBUNGAN PERILAKU MENCUCI TANGAN PENGASUH DENGAN KEJADIAN DIARE PADA BALITA DI DESA TALAGA KECAMATAN GANDING KABUPATEN SUMENEP - Ali Wahyudi; Rifmi Utami; Zakiyah Yasin (Wiraraja Medika : Jurnal Kesehatan, 2014)
Introduction: Diarrheal disease is still one of the major diseases in infants and children in Indonesia. Patients with diarrhea in young children in the village of Talaga reaches 24.1% of the total number of children under five in the village of Talaga. This study aims to determine the relationship of the caregiver handwashing behavior with incidence of diarrhea in children under five in the Talaga village of Subdistrict Ganding 2014.Methods: The research method using analytical design with cross sectional design. Its population is around the caregivers who have children in as many as 191 people Talaga village, with a sample of 64 people were selected using simple random sampling. Data were collected by questionnaires and observationsResult and analiysis: The results showed that the caregiver handwashing behavior in the village of Talaga nearly half (32.8%) handwash well enough behaved, most (60.9%) are less well behaved handwash, and a small proportion (6.3%) did not behave both. On the incidence of diarrhea, most (57.8%) experienced diarrhea toddler caregivers and nearly half (42.2%) did not experience diarrhea. Perform data analysis and statistical tests using the Wilcoxon test, the results obtained pvalue = 0.000 <0.05 with p <α, then there is a relationship with a caregiver handwashing behavior incidence of diarrhea in children under five in the village of Subdistrict Talaga Ganding 2014.. Conclusion: Need for cooperation between the parties and village health workers to perform routine counseling on caregivers toddlers in the village of Talaga on how to prevent diarrhea, especially in performing good hand washing and correct. Keyword: Toddler Diarrhea, Caregivers, Handwashing Behavior.